Effects of aerobic exercise on blood glucose in continuous ambulatory peritoneal dialysis patients - Shahgholian, Nahid (Iran J Nurs Midwifery Res, 2015)
BACKGROUND: Peritoneal dialysis has a number of complications including increased blood glucose. Although exercise has been suggested to resolve this complication, most patients are not active. The present study aimed at determining the effects of twice-weekly, 40-min sessions of pedaling on a stationary bicycle on mean fasting blood sugar (FBS) and 2-h postprandial blood sugar (PPBS) among continuous ambulatory peritoneal dialysis patients. MATERIALS AND METHODS: In this clinical trial, convenience sampling was used to select 22 patients [age: 51.4 (12.3) years] undergoing continuous ambulatory peritoneal dialysis [mean duration: 12.5 (8.5) months] from university hospitals in Isfahan, Iran. The subjects were randomly divided into two groups (test and control). The test group participated in an 8-week exercise program in which they pedaled a stationary bicycle with an intensity of four on Borg Scale of Perceived Exertion. FBS and PPBS were measured at baseline and at the end of the 8(th) and 16(th) sessions of exercise. Data were analyzed with Student's t-test and repeated measures analysis of variance. RESULTS: After the eighth session, the mean FBS and PPBS levels were lower in the test group than in the control group. However, the differences were not statistically significant. After 16 sessions of exercise, the mean FBS and PPBS levels in the intervention group were significantly less than the in control group. CONCLUSIONS: Forty minutes of pedaling on a stationary bicycle for two times a week can significantly reduce mean FBS and PPBS levels in continuous ambulatory peritoneal dialysis patients.